Początki polskiego mennictwa w świetle nowszych badań - Suchodolski, Stanisław (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
The author updates the knowledge of the origins of coinage in Poland in the late 10th and the early 11th centuries. This is possible owing to new coin finds and new research methods, predominantly discoveries of new die-links. In the conclusions, the author states that coin minting in Poland was not initiated by duke Mieszko I (approx. 962-992) but his son Bolesław the Brave (992-1025). The early coinage was more intense than historians used to think, and more diverse. One mint used, simultaneously, dies with correct legends and dies ineptly copying foreign patterns. The coins were used for manifestation and economic purposes alike. They accounted for a small proportion of the prevailing foreign coins in circulation.